Expanding Aquatic Observations through Recreation - Brewin, Robert J. W.; Hyder, Kieran; Andersson, Andreas J.; Billson, Oliver; Bresnahan, Philip J.; Brewin, Thomas G.; Cyronak, Tyler; Dall'Olmo, Giorgio; de Mora, Lee; Graham, George; Jackson, Thomas; Raitsos, Dionysios E. (Frontiers in Marine Science, 2017)
Accurate observations of the Earth system are required to understand how our planet is changing and to help manage its resources. The aquatic environment−including lakes, rivers, wetlands, estuaries, coastal and open oceans−is a fundamental component of the Earth system controlling key physical, biological, and chemical processes that allow life to flourish. Yet, this environment is critically undersampled in both time and space. New and cost-effective sampling solutions are urgently needed. Here, we highlight the potential to improve aquatic sampling by tapping into recreation. We draw attention to the vast number of participants that engage in aquatic recreational activities and argue, based on current technological developments and recent research, that the time is right to employ recreational citizens to improve large-scale aquatic sampling efforts. We discuss the challenges that need to be addressed for this strategy to be successful (e.g. sensor package design, data quality, and citizen motivation), the steps needed to realize its potential, and additional societal benefits that arise when engaging citizens in scientific sampling.